Effect of Green Light from Doubled Frequency Neodymium-Doped Yttrium Aluminum Garnet (Nd:YAG) Laser in the Nanosecond Range on Rabbit’s Lens –In Vitro Study - Abdelkawi, Salwa Ahmed; Hassan, Nahed; Khafagi, Monazah (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: The unprotected eye is extremely sensitive to laser radiation and can be permanently damaged from direct or reflected beams. The area of the eye damaged by laser energy is dependent upon the wavelength of the incident laser beam, duration of exposure and tissue characteristics. This study aims to investigate the effect of intense green light from doubled frequency Neodymium-Doped Yttrium Aluminum Garnet (Nd:YAG) (532nm) in the nanosecond range on the protein of rabbits lenses after short and prolonged (6, 18 seconds) exposures. METHODS: The fundamental wavelength (1064 nm) was frequency doubled in β- Barium Borate (BBO) crystal for second harmonic generation (SHG). Rabbits’ lenses were irradiated in vitro, and the effect of the laser was evaluated by comparing the protein concentration, structure and conformation by sodium dodecyle sulphate polyacrylamide electrophoresis (SDS-PAGE) and Fourier transform infrared spectroscopy (FTIR). RESULTS: The results indicated a significant change in the soluble protein content, the molecular weights and the backbone structure of different lens crystallin fractions. These effects were more distinct when using laser with prolonged irradiation for 18 seconds than for 6 seconds. <span style="font-family: "Verdana","sans-serif"; color: black; font-size: 7pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">CONCLUSION: <span style="font-family: "Verdana","sans-serif"; color: black; font-size: 7pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Irradiation with frequency doubled Nd-YAG green laser seem to be cataractous if the lens is exposed to laser that is intense enough to warrant thermal protein aggregation, folding and denaturation